High-Fat Breakfast Increases Bioavailability of Albendazole Compared to Low-Fat Breakfast: Single-Dose Study in Healthy Subjects - Ochoa, Dolores; Saiz-Rodríguez, Miriam; González-Rojano, Esperanza; Román, Manuel; Sánchez-Rojas, Sergio; Wojnicz, Aneta; Ruiz-Nuño, Ana; García-Arieta, Alfredo; Abad-Santos, Francisco (Frontiers in Pharmacology, 2021)
PURPOSE – Albendazole is a benzoimidazole carbamate drug with anthelmintic and antiprotozoal activity against intestinal and tissue parasites. It has been described that the administration with meals increases albendazole absorption. Our aim was to compare the systemic exposure in healthy volunteers of two albendazole formulations after a single oral dose under fed conditions and to evaluate the effect of breakfast composition on its bioavailability. METHODS – 12 healthy volunteers were included in a crossover, open, randomized comparative bioavailability trial including two stages. Single oral doses of 400 mg albendazole were administered under fed conditions (a light breakfast in first stage and a high-fat breakfast in the second) separated by 7-day washout periods. Plasma albendazole and albendazole sulfoxide concentrations were measured by HPLC-MS/MS. FINDINGS – Albendazole absorption was clearly influenced by the meal composition. A high-fat breakfast increased albendazole and albendazole sulfoxide area under the concentration-time curve (AUC) and maximum concentration (Cmax) by double compared to a light breakfast. The bioavailability of the two formulations was very similar, although the sample size was not sufficient to demonstrate bioequivalence because the intra-individual variability of albendazole was approximately 60%. IMPLICATIONS – The higher albendazole and albendazole sulfoxide levels when administered with a high-fat meal could be of importance in clinical practice. Since albendazole labelling recommends its administration with meals, it is necessary to insist the patient to take it with a fatty meal so that the effectiveness of albendazole is not compromised.